HUBUNGAN SIKAP IBU DAN PERAN KADER DENGAN PEMBERIAN VITAMIN A PADA BALITA USIA 6 – 59 BULAN DI WILAYAH KERJA PUSKESMAS AIR TAWAR TAHUN 2023 - Trisnadewi, Eliza; Putri, Gusliani Eka; Azzahra, Aulia; Yuliva, Yuliva; Sary, Annisa Novita (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Vitamin A deficiency can cause toddlers to easily experience infections and result in blindness. In the city of Padang, the Air Tawar Community Health Center is the community health center with the lowest coverage and has experienced a decrease in the coverage of Vitamin A administration for 3 consecutive years. The aim of this research is to determine the relationship between maternal attitudes and the role of cadres with the provision of Vitamin A to Toddlers aged 6-59 months in the Fresh Air Health Center Work Area in 2023. This type of research is analytical with a cross sectional research design. The population of this study were all children aged 6-59 months with a sample of 132 using simple random sampling techniques. Data were processed and analyzed using the chi-square test. The research results showed that (50.8%) of the respondents were not given vitamin A, there were (65.2%) who had a negative attitude, there were (69.7%) who had a good cadre role, there was a relationship between the mother's attitude and giving vitamin A (p=0.000) and there was a relationship between the role of cadres and giving vitamin A (p=0.000). It can be concluded that it is proven that there is a relationship between the mother's attitude and the role of cadres towards giving vitamin A to toddlers in the Tawar Air Community Health Center Working Area in 2023. It is hoped that the community health center will further increase education about the benefits of Vitamin A to encourage positive attitudes in the community in providing Vitamin A supplements to children. Apart from that, the active role of health cadres is very important in providing education, motivating families, and ensuring that the distribution of Vitamin A supplements goes well.Keywords: Vitamin A administration, mother's attitude, cadre role.